2019
DOI: 10.1016/j.yebeh.2018.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Psychological trauma, somatization, dissociation, and psychiatric comorbidities in patients with psychogenic nonepileptic seizures compared with those in patients with intractable partial epilepsy

Abstract: The objective of this study was to compare patients with intractable epilepsy with patients with psychogenic nonepileptic seizures (PNES) on the presence of psychological traumas, clinical factors, and psychological measures of somatization and dissociation. Background: Several studies have reported a high prevalence of psychological trauma in patients with PNES, while less have examined the prevalence of psychological trauma in patients with epilepsy and compared both groups. Reports have been somewhat diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Elevated somatoform symptoms have been associated with exposure to psychological trauma [21] which is a common risk factor in this group of patients. Excessive concern for bodily symptoms has been reported previously in other samples of PNES patients [22].…”
Section: Discussionsupporting
confidence: 57%
“…Elevated somatoform symptoms have been associated with exposure to psychological trauma [21] which is a common risk factor in this group of patients. Excessive concern for bodily symptoms has been reported previously in other samples of PNES patients [22].…”
Section: Discussionsupporting
confidence: 57%
“…The pooled frequency of epilepsy among patients with PNES is ∼22% (7). Several studies demonstrated a high rate of psychiatric disorders in patients affected by pure PNES (pPNES), and similarly a high frequency of anxiety disorders, affective disorders, and other psychiatric disorders was also described in patients with PNES with comorbid epilepsy (PNES/ES) (4,6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…This background significantly increases their distress and handicap. In addition, Myers et al (14) showed that patients with PNES diagnoses exhibited significantly higher rates of sexual and “other” trauma compared with those with intractable epilepsy. However, subgroup analyses revealed that a history of psychological trauma was the only variable found to discriminate between patients with PNES and those with epilepsy.…”
Section: Introductionmentioning
confidence: 99%